N-tert-Butanesulfinyl imines in the asymmetric synthesis of nitrogen-containing heterocycles - Mendes, Joseane A.; Costa, Paulo R. R.; Yus, Miguel; Foubelo, Francisco; Buarque, Camilla D. (Beilstein Journal of Organic Chemistry, 2021)
The synthesis of nitrogen-containing heterocycles, including natural alkaloids and other compounds presenting different types of biological activities have proved to be successful employing chiral sulfinyl imines derived from tert-butanesulfinamide. These imines are versatile chiral auxiliaries and have been extensively used as eletrophiles in a wide range of reactions. The electron-withdrawing sulfinyl group facilitates the nucleophilic addition of organometallic compounds to the iminic carbon with high diastereoisomeric excess and the free amines obtained after an easy removal of the tert-butanesulfinyl group can be transformed into enantioenriched nitrogen-containing heterocycles. The goal of this review is to the highlight enantioselective syntheses of heterocycles involving the use of chiral N-tert-butanesulfinyl imines as reaction intermediates, including the synthesis of several natural products. The synthesis of nitrogen-containing heterocycles in which the nitrogen atom is not provided by the chiral imine will not be considered in this review. The sections are organized according to the size of the heterocycles. The present work will comprehensively cover the most pertinent contributions to this research area from 2012 to 2020. We regret in advance that some contributions are excluded in order to maintain a concise format.
Keywords: asymmetric synthesis; chiral auxiliary; natural products; nitrogen-containing heterocycles; N-tert-butanesulfinyl imines

(untitled) - Robak, M. T.; Herbage, M. A.; Ellman, J. A. (Chem. Rev., 2010)

(untitled) - Ferreira, F.; Botuha, C.; Chemla, F.; Pérez-Luna, A. (Chem. Soc. Rev., 2009)

(untitled) - Morton, D.; Stockman, R. A. (Tetrahedron, 2006)

(untitled) - Wakayama, M.; Ellman, J. A. (J. Org. Chem., 2009)

(untitled) - Aggarwal, V. K.; Barbero, N.; McGarrigle, E. M.; Mickle, G.; Navas, R.; Suárez, J. R.; Unthank, M. G.; Yar, M. (Tetrahedron Lett., 2009)

(untitled) - Xia, M.-M.; Li, F.-X.; Ma, Y.-P.; Song, L.-L.; Hou, Y.-N.; Shi, Z.-F.; Cao, X.-P. (Adv. Synth. Catal., 2020)

(untitled) - Ye, W.; Zhang, L.; Ni, C.; Rong, J.; Hu, J. (Chem. Commun., 2014)

(untitled) - Kokkonda, P.; Andrade, R. B. (Org. Lett., 2019)

(untitled) - Liu, H.; Zhang, X.; Shan, D.; Pitchakuntla, M.; Ma, Y.; Jia, Y. (Org. Lett., 2017)

(untitled) - Kazak, M.; Priede, M.; Shubin, K.; Bartrum, H. E.; Poisson, J.-F.; Suna, E. (Org. Lett., 2017)

(untitled) - Shao, L.-P.; Si, C.-M.; Mao, Z.-Y.; Zhou, W.; Molinski, T. F.; Wei, B.-G.; Lin, G.-Q. (Org. Chem. Front., 2017)

(untitled) - Tao, W.; Zhou, W.; Zhou, Z.; Si, C.-M.; Sun, X.; Wei, B.-G. (Tetrahedron, 2016)

(untitled) - Zhou, W.; Nie, X.-D.; Zhang, Y.; Si, C.-M.; Zhou, Z.; Sun, X.; Wei, B.-G. (Org. Biomol. Chem., 2017)

(untitled) - Cogan, D. A.; Liu, G.; Kim, K.; Backes, B. J.; Ellman, J. A. (J. Am. Chem. Soc., 1998)

(untitled) - Cogan, D. A.; Ellman, J. A. (J. Am. Chem. Soc., 1999)

(untitled) - Liu, G.; Cogan, D. A.; Owens, T. D.; Tang, T. P.; Ellman, J. A. (J. Org. Chem., 1999)

(untitled) - Jiang, Z.-Y.; Chan, W. H.; Lee, A. W. M. (J. Org. Chem., 2005)

(untitled) - Higashibayashi, S.; Tohmiya, H.; Mori, T.; Hashimoto, K.; Nakata, M. (Synlett, 2004)

(untitled) - Huang, Z.; Zhang, M.; Wang, Y.; Qin, Y. (Synlett, 2005)

(untitled) - Collados, J. F.; Toledano, E.; Guijarro, D.; Yus, M. (J. Org. Chem., 2012)

(untitled) - Tabet, S.; Rodeville, N.; Boiteau, J.-G.; Cardinaud, I. (Org. Process Res. Dev., 2016)

(untitled) - Davis, F. A.; Friedman, A. J.; Kluger, E. W. (J. Am. Chem. Soc., 1974)

(untitled) - Davis, F. A.; Reddy, R. T.; Reddy, R. E. (J. Org. Chem., 1992)

(untitled) - Davis, F. A.; Reddy, R. E.; Szewczyk, J. M.; Portonovo, P. S. (Tetrahedron Lett., 1993)

(untitled) - Davis, F. A.; Zhou, P.; Reddy, G. V. (J. Org. Chem., 1994)

(untitled) - Davis, F. A.; Liu, H.; Zhou, P.; Fang, T.; Reddy, G. V.; Zhang, Y. (J. Org. Chem., 1999)

(untitled) - Davis, F. A.; Reddy, R. E.; Portonovo, P. S. (Tetrahedron Lett., 1994)

(untitled) - Davis, F. A.; Srirajan, V.; Titus, D. D. (J. Org. Chem., 1999)

(untitled) - Jiang, J.; Schumacher, K. K.; Joullié, M. M.; Davis, F. A.; Reddy, R. E. (Tetrahedron Lett., 1994)

(untitled) - Davis, F. A.; McCoull, W.; Titus, D. D. (Org. Lett., 1999)

(untitled) - Davis, F. A. (J. Org. Chem., 2006)

(untitled) - Cainelli, G.; Panunzio, M.; Giacomini, D. (Tetrahedron Lett., 1991)

(untitled) - Davis, F. A.; Zhang, Y.; Rao, A.; Zhang, Z. (Tetrahedron, 2001)

(untitled) - Borg, G.; Cogan, D. A.; Ellman, J. A. (Tetrahedron Lett., 1999)

(untitled) - Kochi, T.; Ellman, J. A. (J. Am. Chem. Soc., 2004)

(untitled) - Colyer, J. T.; Andersen, N. G.; Tedrow, J. S.; Soukup, T. S.; Faul, M. M. (J. Org. Chem., 2006)

(untitled) - Gatling, S. C.; Jackson, J. E. (J. Am. Chem. Soc., 1999)

(untitled) - Wigfield, D. C.; Gowland, F. W. (J. Org. Chem., 1977)

(untitled) - Sirvent, A.; Foubelo, F. (Lett. Org. Chem., 2018)

(untitled) - Mejuch, T.; Gilboa, N.; Gayon, E.; Wang, H.; Houk, K. N.; Marek, I. (Acc. Chem. Res., 2013)

(untitled) - Zimmerman, H. E.; Traxler, M. D. (J. Am. Chem. Soc., 1957)

(untitled) - Yamamoto, Y.; Asao, N. (Chem. Rev., 1993)

(untitled) - Yamamoto, Y.; Komatsu, T.; Maruyama, K. (J. Org. Chem., 1985)

(untitled) - Plobeck, N.; Powell, D. (Tetrahedron: Asymmetry, 2002)

(untitled) - Pflum, D. A.; Krishnamurthy, D.; Han, Z.; Wald, S. A.; Senanayake, C. H. (Tetrahedron Lett., 2002)

(untitled) - Almansa, R.; Guijarro, D.; Yus, M. (Tetrahedron: Asymmetry, 2008)

(untitled) - Almansa, R.; Guijarro, D.; Yus, M. (Tetrahedron: Asymmetry, 2008)

(untitled) - Almansa, R.; Guijarro, D.; Yus, M. (Tetrahedron Lett., 2009)

(untitled) - Almansa, R.; Collados, J. F.; Guijarro, D.; Yus, M. (Tetrahedron: Asymmetry, 2010)

(untitled) - González-Gómez, J. C.; Medjahdi, M.; Foubelo, F.; Yus, M. (J. Org. Chem., 2010)

(untitled) - McCoull, W.; Davis, F. A. (Synthesis, 2000)

(untitled) - Bulut, A.; Aslan, A.; Dogan, Ö. (J. Org. Chem., 2008)

(untitled) - Chi, Y.; Scroggins, S. T.; Boz, E.; Fréchet, J. M. J. (J. Am. Chem. Soc., 2008)

(untitled) - Song, X.; Hua, Y.-Z.; Shi, J.-G.; Sun, P.-P.; Wang, M.-C.; Chang, J. (J. Org. Chem., 2014)

(untitled) - Pieczonka, A. M.; Jarzyński, S.; Wujkowska, Z.; Leśniak, S.; Rachwalski, M. (Tetrahedron Lett., 2015)

(untitled) - Rachwalski, M.; Jarzyński, S.; Jasiński, M.; Leśniak, S. (Tetrahedron: Asymmetry, 2013)

(untitled) - Tanner, D. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Sweeney, J. B. (Chem. Soc. Rev., 2002)

(untitled) - Degennaro, L.; Trinchera, P.; Luisi, R. (Chem. Rev., 2014)

(untitled) - Ohno, H. (Chem. Rev., 2014)

(untitled) - Sabir, S.; Kumar, G.; Jat, J. L. (Asian J. Org. Chem., 2017)

(untitled) - Morton, D.; Pearson, D.; Field, R. A.; Stockman, R. A. (Synlett, 2003)

(untitled) - Fernández, I.; Valdivia, V.; Gori, B.; Alcudia, F.; Álvarez, E.; Khiar, N. (Org. Lett., 2005)

(untitled) - Li, Y.; Ma, Y.; Lu, Z.; Wang, L.; Ren, X.; Sun, Z. (Tetrahedron Lett., 2012)

(untitled) - García Ruano, J.; Fernández, I.; Prado Catalina, M. d.; Cruz, A. A. (Tetrahedron: Asymmetry, 1996)

(untitled) - Yus, M.; González-Gómez, J. C.; Foubelo, F. (Chem. Rev., 2013)

(untitled) - Foubelo, F.; Yus, M. (Eur. J. Org. Chem., 2014)

(untitled) - Liu, W.-J.; Zhao, Y.-H.; Sun, X.-W. (Tetrahedron Lett., 2013)

(untitled) - Maciá, E.; Foubelo, F.; Yus, M. (Heterocycles, 2019)

(untitled) - Moragas, T.; Churcher, I.; Lewis, W.; Stockman, R. A. (Org. Lett., 2014)

(untitled) - Zhang, Y.; Tian, H.; Luo, Z.; Liu, X.; Zhao, Y.; Chen, W.; Zhang, H. (Tetrahedron Lett., 2018)

(untitled) - Chogii, I.; Das, P.; Delost, M. D.; Crawford, M. N.; Njardarson, J. T. (Org. Lett., 2018)

(untitled) - Huang, Z.-A.; Liu, H.; Lu, C.-D.; Xu, Y.-J. (Org. Lett., 2015)

(untitled) - Yang, Y.; Huang, Y.; Qing, F.-L. (Tetrahedron Lett., 2013)

(untitled) - Qin, S.; Yao, L.; Luo, Y.; Liu, T.; Xu, J.; Sun, Y.; Wang, N.; Yan, J.; Tang, B.; Yang, G.; Yang, C. (Org. Chem. Front., 2020)

(untitled) - Reidl, T. W.; Anderson, L. L. (Asian J. Org. Chem., 2019)

(untitled) - Andresini, M.; Degennaro, L.; Luisi, R. (Org. Biomol. Chem., 2020)

(untitled) - Arya, N.; Jagdale, A. Y.; Patil, T. A.; Yeramwar, S. S.; Holikatti, S. S.; Dwivedi, J.; Shishoo, C. J.; Jain, K. S. (Eur. J. Med. Chem., 2014)

(untitled) - Gandhi, D.; Kalal, P.; Agarwal, S. (Chem. Biol. Interface, 2017)

(untitled) - Zachariah, S. M.; Ramkumar, M.; George, N.; Ashif, M. S. (Int. J. Pharm. Sci. Rev. Res., 2015)

(untitled) - Reddy, L. R.; Waman, Y.; Kallure, P.; Nalivela, K. S.; Begum, Z.; Divya, T.; Kotturi, S. (Chem. Commun., 2019)

(untitled) - Reddy, L. R.; Waman, Y.; Nayak, K.; Baharooni, K.; Kotturi, S. (Org. Lett., 2019)

(untitled) - Lima, L. M.; da Silva, B. N. M.; Barbosa, G.; Barreiro, E. J. (Eur. J. Med. Chem., 2020)

(untitled) - Delgado, O.; Monteagudo, A.; Van Gool, M.; Trabanco, A. A.; Fustero, S. (Org. Biomol. Chem., 2012)

(untitled) - Edupuganti, R.; Davis, F. A. (Org. Biomol. Chem., 2012)

(untitled) - Albrecht, B. K.; Gehling, V. S.; Hewitt, M. C.; Vaswani, R. G.; Côté, A.; Leblanc, Y.; Nasveschuk, C. G.; Bellon, S.; Bergeron, L.; Campbell, R.; Cantone, N.; Cooper, M. R.; et al. (J. Med. Chem., 2016)

(untitled) - Yang, X.-d.; Dong, C.-m.; Chen, J.; Ding, Y.-h.; Liu, Q.; Ma, X.-y.; Zhang, Q.; Chen, Y. (Chem. – Asian J., 2013)

(untitled) - Su, L.; Xu, M.-H. (Synthesis, 2016)

(untitled) - Dema, H. K.; Foubelo, F.; Yus, M. (Helv. Chim. Acta, 2012)

(untitled) - Lin, Y.-C.; Ribaucourt, A.; Moazami, Y.; Pierce, J. G. (J. Am. Chem. Soc., 2020)

(untitled) - Adrio, J.; Carretero, J. C. (Chem. Commun., 2019)

(untitled) - Nájera, C.; Sansano, J. M. (Pure Appl. Chem., 2019)

(untitled) - Upadhyay, P.; Srivastava, V. (Curr. Organocatal., 2016)

(untitled) - Rajput, A. P.; Nagarale, D. V. (J. Chem. Pharm. Res., 2016)

(untitled) - Reddy, L. R.; Gupta, A. P.; Villhauer, E.; Liu, Y. (J. Org. Chem., 2012)

(untitled) - Fustero, S.; Herrera, L.; Lázaro, R.; Rodríguez, E.; Maestro, M. A.; Mateu, N.; Barrio, P. (Chem. – Eur. J., 2013)

(untitled) - Redford, J. E.; McDonald, R. I.; Rigsby, M. L.; Wiensch, J. D.; Stahl, S. S. (Org. Lett., 2012)

(untitled) - Zhou, Q.-R.; Wei, X.-Y.; Li, Y.-Q.; Huang, D.; Wei, B.-G. (Tetrahedron, 2014)

(untitled) - Si, C.-M.; Mao, Z.-Y.; Liu, Y.-W.; Du, Z.-T.; Wei, B.-G.; Lin, G.-Q. (Org. Chem. Front., 2015)

(untitled) - Si, C.-M.; Shao, L.-P.; Mao, Z.-Y.; Zhou, W.; Wei, B.-G. (Org. Biomol. Chem., 2017)

(untitled) - Chogii, I.; Njardarson, J. T. (Angew. Chem., Int. Ed., 2015)

(untitled) - Xu, C.-P.; Huang, P.-Q.; Py, S. (Org. Lett., 2012)

(untitled) - Maciá, E.; Foubelo, F.; Yus, M. (Tetrahedron, 2016)

(untitled) - Procopiou, G.; Lewis, W.; Harbottle, G.; Stockman, R. A. (Org. Lett., 2013)

(untitled) - Mendes, J. A.; Merino, P.; Soler, T.; Salustiano, E. J.; Costa, P. R. R.; Yus, M.; Foubelo, F.; Buarque, C. D. (J. Org. Chem., 2019)

(untitled) - Li, Y.; Xu, M.-H. (Org. Lett., 2012)

(untitled) - Green, B. T.; Lee, S. T.; Panter, K. E.; Brown, D. R. (Food Chem. Toxicol., 2012)

(untitled) - Kittakoop, P.; Mahidol, C.; Ruchirawat, S. (Curr. Top. Med. Chem., 2014)

(untitled) - Zhao, G.; Canterbury, D. P.; Taylor, A. P.; Cheng, X.; Mikochik, P.; Bagley, S. W.; Tong, R. (Org. Lett., 2020)

(untitled) - Bari, A.; Iqbal, A.; Khan, Z. A.; Shahzad, S. A.; Yar, M. (Synth. Commun., 2020)

(untitled) - Brahmachari, G.; Das, S. (Tetrahedron Lett., 2012)

(untitled) - Fustero, S.; Jiménez, D.; Moscardó, J.; Catalán, S.; del Pozo, C. (Org. Lett., 2007)

(untitled) - Lebold, T. P.; Leduc, A. B.; Kerr, M. A. (Org. Lett., 2009)

(untitled) - Dobbs, A. P.; Guesné, S. J. J. (Synlett, 2005)

(untitled) - Sales, M.; Charette, A. B. (Org. Lett., 2005)

(untitled) - Merino, P.; Tejero, T.; Greco, G.; Marca, E.; Delso, I.; Gómez-SanJuan, A.; Matute, R. (Heterocycles, 2012)

(untitled) - Buffat, M. G. P. (Tetrahedron, 2004)

(untitled) - Laschat, S.; Dickner, T. (Synthesis, 2000)

(untitled) - Sirvent, J. A.; Foubelo, F.; Yus, M. (Heterocycles, 2014)

(untitled) - Lahosa, A.; Soler, T.; Arrieta, A.; Cossío, F. P.; Foubelo, F.; Yus, M. (J. Org. Chem., 2017)

(untitled) - Bosque, I.; González-Gómez, J. C.; Foubelo, F.; Yus, M. (J. Org. Chem., 2012)

(untitled) - González-Gómez, J. C.; Foubelo, F.; Yus, M. (Synlett, 2008)

(untitled) - Reddy, A. A.; Prasad, K. R. (J. Org. Chem., 2017)

(untitled) - Si, C.-M.; Huang, W.; Du, Z.-T.; Wei, B.-G.; Lin, G.-Q. (Org. Lett., 2014)

(untitled) - Han, P.; Si, C.-M.; Mao, Z.-Y.; Li, H.-T.; Wei, B.-G.; Du, Z.-T. (Tetrahedron, 2016)

(untitled) - Wang, C.; Liu, Y.-W.; Zhou, Z.; Si, C.-M.; Sun, X.; Wei, B.-G. (Tetrahedron, 2018)

(untitled) - Si, C.-M.; Mao, Z.-Y.; Zhou, Z.; Du, Z.-T.; Wei, B.-G. (Tetrahedron, 2015)

(untitled) - Liu, Y.-W.; Mao, Z.-Y.; Ma, R.-J.; Yan, J.-H.; Si, C.-M.; Wei, B.-G. (Tetrahedron, 2017)

(untitled) - Zhang, Z.; Sun, Z. (Synlett, 2020)

(untitled) - Zhou, W.; Zhang, Y.-X.; Nie, X.-D.; Si, C.-M.; Sun, X.; Wei, B.-G. (J. Org. Chem., 2018)

(untitled) - Kaczorek, D.; Kawęcki, R. (Tetrahedron Lett., 2020)

(untitled) - Reddy, Y. V.; Biradar, D. O.; Reddy, B. J. M.; Rathod, A.; Himabindu, M.; Reddya, B. V. S. (Nat. Prod. Commun., 2017)

(untitled) - Frederico, D.; Brocksom, U.; Brocksom, T. J. (Quim. Nova, 2005)

(untitled) - Pinto, A.; Griera, R.; Molins, E.; Fernández, I.; Bosch, J.; Amat, M. (Org. Lett., 2017)

(untitled) - Pinto, A.; Piccichè, M.; Griera, R.; Molins, E.; Bosch, J.; Amat, M. (J. Org. Chem., 2018)

(untitled) - Medjahdi, M.; González-Gómez, J. C.; Foubelo, F.; Yus, M. (Heterocycles, 2012)

(untitled) - Sirvent, A.; García-Muñoz, M. J.; Yus, M.; Foubelo, F. (Eur. J. Org. Chem., 2020)

(untitled) - García-Muñoz, M. J.; Foubelo, F.; Yus, M. (J. Org. Chem., 2016)

(untitled) - Penk, D. N.; Robinson, N. A.; Hill, H. M.; Turlington, M. (Tetrahedron Lett., 2017)

(untitled) - Chowdhury, S.; Mao, J.; Martynow, J.; Zhao, H.; Duffy, E.; Wu, Y.; Thakur, V.; Sirasani, G.; Tang, Y.; Collin, F.; Sinishtaj, S.; Bhattacharjee, A. (Tetrahedron Lett., 2019)

(untitled) - Lahosa, A.; Yus, M.; Foubelo, F. (J. Org. Chem., 2019)

(untitled) - García-Muñoz, M. J.; Foubelo, F.; Yus, M. (Heterocycles, 2015)

(untitled) - Hernández-Ibáñez, S.; Soares do Rego Barros, O.; Lahosa, A.; García-Muñoz, M. J.; Benlahrech, M.; Behloul, C.; Foubelo, F.; Yus, M. (Tetrahedron, 2020)

(untitled) - Chen, D.; Xu, M.-H. (Chem. Commun., 2013)

(untitled) - Peralta-Hernández, E.; Cordero-Vargas, A. (Synthesis, 2016)

(untitled) - Babu, R. A.; Reddy, N. S. S.; Reddy, B. J. M.; Reddy, B. V. S. (Synthesis, 2014)

(untitled) - Reddy, N. S. S.; Reddy, B. V. S. (Tetrahedron Lett., 2014)

(untitled) - Yus, M.; González-Gómez, J. C.; Foubelo, F. (Chem. Rev., 2011)

(untitled) - Foubelo, F.; Yus, M. (Chim. Oggi, 2016)

(untitled) - Reddy, N. S. S.; Reddy, B. J. M.; Reddy, B. V. S. (Tetrahedron Lett., 2013)

(untitled) - Reddy, N. S. S.; Babu, R. A.; Reddy, B. V. S. (Synthesis, 2016)

(untitled) - Bosque, I.; Gonzalez-Gomez, J. C.; Loza, M. I.; Brea, J. (J. Org. Chem., 2014)

(untitled) - Bosque, I.; González-Gómez, J. C.; Guijarro, A.; Foubelo, F.; Yus, M. (J. Org. Chem., 2012)

(untitled) - Anton-Torrecillas, C.; Gonzalez-Gomez, J. C. (Org. Biomol. Chem., 2014)

(untitled) - Anton-Torrecillas, C.; Bosque, I.; Gonzalez-Gomez, J. C.; Loza, M. I.; Brea, J. (J. Org. Chem., 2015)

(untitled) - Anton-Torrecillas, C.; Loza, M. I.; Brea, J.; Gonzalez-Gomez, J. C. (Org. Biomol. Chem., 2016)

(untitled) - Sirvent, J. A.; Foubelo, F.; Yus, M. (J. Org. Chem., 2014)

(untitled) - Liu, Y.-W.; Han, P.; Zhou, W.; Mao, Z.-Y.; Si, C.-M.; Wei, B.-G. (Org. Biomol. Chem., 2016)

(untitled) - Uphade, M. B.; Reddy, A. A.; Khandare, S. P.; Prasad, K. R. (Org. Lett., 2019)

(untitled) - Guerola, M.; Sánchez-Roselló, M.; Mulet, C.; del Pozo, C.; Fustero, S. (Org. Lett., 2015)

(untitled) - Fadeyi, O. O.; Senter, T. J.; Hahn, K. N.; Lindsley, C. W. (Chem. – Eur. J., 2012)

(untitled) - Senter, T. J.; Fadeyi, O. O.; Lindsley, C. W. (Org. Lett., 2012)

(untitled) - Si, C.-M.; Mao, Z.-Y.; Dong, H.-Q.; Du, Z.-T.; Wei, B.-G.; Lin, G.-Q. (J. Org. Chem., 2015)

(untitled) - Zhang, W.; Sha, W.; Zhu, Y.; Han, J.; Soloshonok, V. A.; Pan, Y. (Eur. J. Org. Chem., 2017)

(untitled) - Thaisrivongs, D. A.; Miller, S. P.; Molinaro, C.; Chen, Q.; Song, Z. J.; Tan, L.; Chen, L.; Chen, W.; Lekhal, A.; Pulicare, S. K.; Xu, Y. (Org. Lett., 2016)

(untitled) - Hugelshofer, C. L.; Palani, V.; Sarpong, R. (J. Org. Chem., 2019)

(untitled) - Benlahrech, M.; Lahosa, A.; Behloul, C.; Foubelo, F.; Yus, M. (Heterocycles, 2018)

(untitled) - Reddy, A. A.; Reddy, P. O.; Prasad, K. R. (J. Org. Chem., 2016)

(untitled) - Chatare, V. K.; Andrade, R. B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Walia, M.; Teijaro, C. N.; Gardner, A.; Tran, T.; Kang, J.; Zhao, S.; O’Connor, S. E.; Courdavault, V.; Andrade, R. B. (J. Nat. Prod., 2020)

(untitled) - Zhao, S.; Andrade, R. B. (J. Org. Chem., 2017)

(untitled) - Zhao, S.; Andrade, R. B. (J. Am. Chem. Soc., 2013)

(untitled) - Si, C.-M.; Liu, Y.-W.; Mao, Z.-Y.; Han, P.; Du, Z.-T.; Wei, B.-G. (Tetrahedron, 2016)

(untitled) - Liu, Q.; Zhang, Y.-A.; Xu, P.; Jia, Y. (J. Org. Chem., 2013)